Histórico e implementação de sistemas de Pagamentos Por Serviços Ambientais no Estado de Minas Gerais - Oliveira, Ana Carolina Campanha de; Vilar, Mariana Barbosa; Jacovine, Laércio Antônio Gonçalves; Santos, Marcelo Oliveira; Jacon, Aline Daniele (Sustainability in Debate, 2013)
Different initiatives of Payment for Ecosystem Services (PES) are already happening in Brazil and around the world. In Brazil, one of them is the “Green Grant” Program (Bolsa Verde). This program is a political and economic instrument practiced in the state of Minas Gerais. It allows, through annual remuneration, the recognition of farmers who provide ecosystem services in their properties. In this context, this article aims at performing a brief history and analysis of the implementation of PES programs in Minas Gerais from two initiatives: the Green Grant program and the Environmental Agent program. The latter is being developed in response to the guidelines established by the Green Grant program. It is possible to assert that for the success of PES systems it is important to integrate different actors to ensure technical assistance, information access and contracts durability. PES systems tend to combine agricultural production with environmental protection and can help farmers to build a new relation with environmental sustainability. However, the current challenges of PES programs in Minas Gerais indicate that good policy is not sufficient for the program to be successful. PES programs require an efficient institutional arrangement, sustainable funding mechanisms and participatory implementing, involving the main actors of these processes.